Dasar-Dasar Ilmu Falak: Pengenalan terhadap Astronomi dalam Perspektif Islam - Mahmud, Hamdan (Sharia Journal and Education Center Publishing, 2024)
Ilmu falak, or Islamic astronomy, is a discipline that studies the movements of celestial bodies such as the sun, moon, stars, and planets. This research aims to outline the basics of ilmu falak and explain its relevance to Islamic teachings. Using a literature review approach, this study examines the fundamental concepts of ilmu falak, its historical development in Islamic civilization, and its relationship with modern astronomy. The results show that ilmu falak plays a crucial role in determining prayer times, the direction of the Qibla, the beginning of the lunar months, and celestial phenomena such as eclipses. Numerous verses in the Qur'an and Hadith emphasize the importance of studying the heavens as signs of Allah's greatness. Thus, ilmu falak is not only a tool for understanding the universe but also a means of drawing closer to the Creator. This article suggests the need for integrating ilmu falak with modern technology and increasing public education about the importance of this science in religious life.